Characterization of Pearl Millet [Pennisetum glaucum (L.) R. Br.] Drought Tolerant Lines Developed for A1 zone Using SSR Markers: SSR marker characterization of pearl millet - Ambawat, Supriya; Meena, RC; Satyavathi, C Tara; Meena, Rajbala; Khandelwal, Vikas; Sewaliya, Mahendra; Kumar, Manoj; Bishnoi, JP; Singh, Subaran (Annals of Arid Zone, 2023)
Pearl millet [Pennisetum glaucum (L.) R. Br] is the fifth most important cereal in the world and is a primary food source of arid and semi-arid tropical regions of Asia and Africa. It is mainly grown over 30 million ha worldwide with majority of the crop grown in Africa and Asia. It is very useful for combating the adverse effects of changing climate and can also ensure livelihood security among farming communities. It has climate-resilient attributes and can grow in less fertile soil even under adverse and harsh climatic conditions. It can show better growth and productivity in low nutrient input conditions and needs lesser synthetic fertilizers and irrigations. Screening and selecting germplasm for drought tolerance and developing drought tolerant hybrids and varieties of pearl millet is very important in the present scenario of global warming and climatic change. In this study, 24 drought tolerant lines of pearl millet developed specifically for A1 zone were characterized using 15 drought specific SSR primers. All the 15 SSRs amplified products of varying sizes ranging from 100-550 bp. A total of 38 alleles were obtained in this study and the number of alleles per locus varied from 2 to 4 with an average of 2.53 alleles. Polymorphic Information Content (PIC) varied from 0.41 to 0.69 with an average of 0.51 PIC value. This study can be highly useful for developing high yielding drought tolerant cultivars for low rainfall areas i.e. A1 zone and increasing pearl millet productivity.